Estimativa da infiltração de água no solo a partir de pedofunções - Fiorin, Tatiana Tasquetto (2008)
Knowledge on soil water infiltration is essential for the solution of problems concerning irrigation and drainage areas and those related to water and soil conservation research. In that regard, the aim of this paper was to model water infiltration rate and hydraulic conductivity in saturated soil by means of pedotransfer functions for soils of various physical characteristics in 16 sites in Rio Grande do Sul and 04 sites in Uruguay. For each site, the following variables were determined: water infiltration rate, density (soil and particle), soil porosity (macro, micro and total), texture (clay, silt and sand), initial soil moisture content, saturation and water content at 1, 6, 10, 100, 500, 1500 KPa, and hydraulic conductivity (which was measured in seven sites only). Experimental water infiltration rate was obtained by use of the Double-ring infiltrometer and data were adjusted with Kostiakov s and Horton s model. Artificial rainfalls were applied by using a simulator with stationary and oscillating nozzles. Six plots measuring 0,5 m2 were delimited by galvanized steel boards inserted into the soil. Each board was equipped with a gutter at the lower part to collect runoff water (measured at 5-minute intervals). Smith s mathematical model as modified by Cabeda was used to describe infiltration rate. Experimental hydraulic conductivity in saturated soil was carried out by using Guelph s parameter. Kostiakov1s, Horton s and Smith s parameters were adjusted by means of multivariate equations. In comparison to Kostiakov s, Horton s model resulted in overestimation of soil water capacity. For Argissolo 01 and 02 and Chernossolo, cross-comparison between Kostiakov and Horton s model and Smith s model revealed overestimation of water infiltration rate by use of Kostiakov and Horton s model. While for Latossolo 12, Neossolo, and Vertissolo 01, water infiltration values were underestimated. In determining multivariate equations for the estimation of Kostiakov and Horton s models parameters, physical-hydraulic variables adopted were density (soil and particle), soil porosity (macro, micro and total), texture (clay, silt and sand), initial soil moisture content and saturation, and water content at 1, 6, 10, 100, 500, 1500 KPa. Such equations performed suitably for all the soils investigated. The pedofunction originated from the correlation between water infiltration rate obtained by means of Kostiakov and Horton s pedofunctions and water infiltration rate obtained by means of Smith s model can adequately predict water infiltration rate as estimated by Smith s model. Obtaining pedofunction equations by use of multivariate equations for estimating hydraulic conductivity in saturated soil solo by Guelph s model is suitable for estimating the model parameters.